Isolation and identification of acetobacter tropicalis from selected Malaysian local fruits for potential BC production - Tan, Yong Jie; Junaidi Zakaria,; Shahril Mohamad,; Chua, Gek Kee; Nurshahqifah Latif,; Mohd Hairul Ab Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Acetobacter spp. that are commonly found on fruits, can perform oxidation processes, resulting in acetic acid production in vinegar. Besides that, Acetobacter spp. able to produce bacterial cellulose (BC), which is an essential by-product. This present study was carried out to isolate Acetobacter spp. from selected local fruits. Species verification of the bacterial isolates was performed using molecular and bioinformatic approaches. A total of six local fruits (starfruit, jackfruit, watermelon, pineapple, honeydew & banana) were subjected to seven days of fermentation in a brown sugar solution. Acetobacter spp. were isolated from the fermented medium using bromocresol green ethanol agar as the selective medium. Thirteen bacterial isolates were obtained and subjected to molecular works, including DNA extraction and PCR amplification using universal primers, targeting the 16S rRNA genes. PCR-amplified products were selected for single-pass sequencing. BLASTn analysis of the sequencing results showed three isolates (23.1%) belonging to Acetobacter tropicalis and one isolate (7.7%) representing Gluconobacter oxydans might have potential in BC production. However, the remaining nine isolates (69.2%) hit the Lactobacillus genus. Morphological observation using FESEM showed that the BC produced by all the positive bacterial isolates is similar to dried nata de coco and BC produced by Acetobacter xylinum. In addition, four similar regions of -OH stretch (3400 - 3300 cm-1), -CH stretch (2970 to 2800 cm-1), -OH bending (1620 cm-1), and -COC stretch (1100 to 1073 cm-1) are identified in the BC samples. In the future, the isolated Acetobacter and Gluconobacter strains could be further utilized for large-scale BC production in a suitable fermentation medium.